ABILITY AS AN IMPORTANT PSYCHOLOGICAL CHARACTERISTIC OF A PERSON (American Journal of Pedagogical and Educational Research, 2023)
This article discusses the psychological characteristics of ability, the structure of ability, its types, qualitative and quantitative description of ability, and who dealt with the problem of ability.